SAMPUL BUKU TULIS SEBAGAI MEDIA PROMOSI KESEHATAN HIV/AIDS SISWA-SISWA SMP DI KABUPATEN WONOGIRI - , SUPARTONO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Wonogiri Regency is one of regencies in Central Java with a very fast increase of HIV/AIDS cases. Effort of health promotion about HIV/AIDS is necessary provided early to people, especially for school-age children. The use of a writing book cover as a medium of health promotion of HIV/AIDS can be considered because it has more advantages than other media and writing book is frequently used for learning activities at school and home. Purpose of the Research: To develop health promotion media about HIV/AIDS in the form of writing book cover for secondary school students in Wonogiri Regency. Method of the Research: The research was a developmental research with qualitative method. Subject of the research were students of secondary school and informants consisting of media practitioner, cultural scientist and observers of HIV/AIDS. Sample is taken in manner of nonprobability sampling by using purposive sampling technique. Data was collected by using documents study, indepth interview, and guided group discussion. Results: The development of health promotion media about HIV/AIDS in the form of writing book cover was conducted through stages of problem analysis, designing, validation of expert team and product trial. Factors need to consider in development of the writing book cover are culture, ethics, target audience, varied illustration, many matching colors, varied letters, using a picture message that is not too vulgar, message contents and their explanations, and use of additional slang. Many responses of the students on the use of writing book cover as health promotion media of HIV/ AIDS, among the others were: attracts attention, change views on HIV/AIDS diseases, suitable for secondary school student and the media is not containing adult elements, the media has many benefits and it has more advantages than other printed media Conclusion: The development of health promotion media about HIV/AIDS in the form of writing book cover should pay attention to culture, ethics, target audience, and graphic design rule. Secondary school students given a positive response using writing book cover as a media of health promotion about HIV/AIDS.